2009
DOI: 10.1519/jsc.0b013e3181bc1c2a
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Blood Flow Restriction on Muscle Activity and Endurance During Fatiguing Dynamic Knee Extensions at Low Load

Abstract: The purpose of this study was to investigate muscle activity and endurance during fatiguing low-intensity dynamic knee extension exercise with and without blood flow restriction. Eleven healthy subjects with strength training experience performed 3 sets of unilateral knee extensions with no relaxation between repetitions to concentric torque failure at 30% of the 1 repetition maximum. One leg was randomized to exercise with cuff occlusion and the other leg to exercise without occlusion. The muscle activity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
164
6
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(198 citation statements)
references
References 23 publications
21
164
6
7
Order By: Relevance
“…Currently, no studies have analyzed muscle soreness associated with BFR resistance exercise in the upper body. Reported muscle soreness in BFR exercise studies have ranged from 33 to 55 mm (VAS, 0-100 mm), following both eccentric and concentric exercise to failure [22,23] but have also been found to be as low as 1.6 on a verbal analog scale (0-10) after only performing ECC-BFR exercise to failure [9]. The muscle soreness levels in this BFR study were smaller than most other BFR studies (20 mm vs. 33-55 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no studies have analyzed muscle soreness associated with BFR resistance exercise in the upper body. Reported muscle soreness in BFR exercise studies have ranged from 33 to 55 mm (VAS, 0-100 mm), following both eccentric and concentric exercise to failure [22,23] but have also been found to be as low as 1.6 on a verbal analog scale (0-10) after only performing ECC-BFR exercise to failure [9]. The muscle soreness levels in this BFR study were smaller than most other BFR studies (20 mm vs. 33-55 mm).…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies measuring muscle activation via electromyography (EMG) during unfatigued contractions demonstrated significantly greater responses with the application of BFR (91,100,101). Conversely, Wernbom et al (97) in examining 3 sets of low--intensity (30% of 1RM) unilateral knee extensions with BFR (100 mm Hg; 135--mm cuff width) and without BFR, found similar EMG activity patterns, with the exception that without BFR, set 3 demonstrated greater EMG activity during the eccentric phase, when all sets were performed to repetition failure. Similarly, Kacin and Strazer (38) evaluated vastus medialis and rectus femoris EMG activity during dynamic knee extensions performed to repetition failure under 2 different conditions: (a) (Con) 15% of MVC without BFR, (b) (Isch) 15% of MVC with BFR at 230 mm Hg.…”
Section: Muscle Fiber Recruitmentmentioning
confidence: 96%
“…However, distinctions have been made between ROS produced chronically during resting conditions, where radicals are primarily generated by the mitochondrial electron transport chain in the beta--oxidation of fatty acids, and those generated transiently by contracting muscles during exercise (6). The ROS have been shown to promote growth in both smooth muscle and cardiac muscle (87), and several researchers have speculated that they might be involved in the hypertrophic response pursuant to BFR (92,94,97). Hornberger et al (35) demonstrated that selenoprotein--deficient transgenic mice exhibited significantly greater increases in exercise--induced muscle growth compared with that in wildtype controls, suggesting an ROS--mediated hypertrophic effect through redox sensitive signaling pathways.…”
mentioning
confidence: 99%
“…Despite evidence concerning fatigue as an active variable in TVO to alter the pattern of recruitment, Wernbom et al [20] found no difference in the pattern of electromyographic (EMG) activity, either in concentric or eccentric contractions of individuals who underwent knee extensions to failure with and without occlusion. In addition, long periods of TVO can reduce EMG activity owing to a probable increase in sensory feedback or increased perceived exertion during occluded exercise, which inhibits motor activity [9].…”
Section: Muscle Fibre Type Recruitmentmentioning
confidence: 99%